Advanced Testing of Soft Polymer Materials - Stoček, Radek; Heinrich, Gert; Kipscholl, Reinhold (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Manufacturers of soft polymer products, as well as suppliers and processors of polymers, raw materials, and compounds or blends are compelled to use predictive and advanced laboratory testing in their search for high-performance soft polymer materials for future applications. The collection of 12 publications contained in this edition therefore presents different methods used to solve problems in the characterization of various phenomena in soft polymer materials, asks relevant questions and offers appropriate solutions.